2015
DOI: 10.1097/shk.0000000000000390
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Rescues Kidney Mitochondrial Function Following Hemorrhagic Shock

Abstract: Objective Hemorrhagic shock may contribute to acute kidney injury by profoundly altering renal mitochondrial function. Resveratrol (RSV), a naturally occurring sirtuin-1 (SIRT1) activator, has been shown to promote mitochondrial function and reduce oxidative damage in a variety of aging-related disease states. We hypothesized that RSV treatment during resuscitation would ameliorate kidney mitochondrial dysfunction and decrease oxidative damage following hemorrhagic shock. Method Using a decompensated hemorrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 37 publications
(20 reference statements)
3
49
0
Order By: Relevance
“…Sodium Azide (2.5 mM) was used to assess the contribution of leak respiration independent of CIV. 37,38 …”
Section: Methodsmentioning
confidence: 99%
“…Sodium Azide (2.5 mM) was used to assess the contribution of leak respiration independent of CIV. 37,38 …”
Section: Methodsmentioning
confidence: 99%
“…Resveratrol attenuates hepatocyte (Powell et al , 2014; Yu et al , 2010b), intestinal (Yu et al , 2011), lung (Wu et al , 2008), kidney(Wang et al , 2015a) and endothelial (Yu et al , 2010a) injury during hemorrhage induced ischemia. The accumulation and activity of the mitochondrial/glycolytic master switch in hypoxia, HIF1-α, is regulated by SIRT1 in hypoxic hepatocellular (Laemmle et al , 2012), kidney, colorectal, gastric cancer, cervical, lung, fibrosarcoma, glioblastoma and prostate cancer cells (Yoon et al , 2014).…”
Section: Pharmacologic Therapiesmentioning
confidence: 99%
“…Furthermore, the decreased oxygen availability in tissues result in declined OXPHOS activity and ATP production. To further confirm the dysregulation of mitochondrial metabolism in HI, our laboratory and others have demonstrated that agents which potentiate mitochondrial function can improve organ function and survival following HI in experimental models of hemorrhagic shock (1820). However, the understanding of the role of mitochondria in HI is still evolving and the effect of HI on splenocyte mitochondrial respiration remains unknown.…”
Section: Introductionmentioning
confidence: 99%